Investigating the Effect of Curing and Thermal Equilibrium Time on Rutting Potential of Hot Mix Asphalt - Ghaffari Jajin, Morteza; Esmaeili, Niloofar; Hamedi, Gholam Hossein (Periodica Polytechnica Civil Engineering, 2021)
Rutting is a common damage of flexible pavements, reducing the service life of asphalt pavement. Due to laboratory limitations, asphalt mixtures are subjected to different curing times (since construction until placement in the test chamber) and thermal equilibrium times (since placement in the test chamber until the beginning of the test) before rutting tests. Neglecting these factors can lead to errors in the laboratory results. Therefore, the present study attempted to investigate the effect of curing times of 1, 2, and 3 days at 25ºC and thermal equilibrium times of 2, 4, and 6 hours on the rutting potential of different hot-mix asphalt (HMA) mixtures. Results of rutting tests showed that the rutting potential of asphalt mixtures decreases by increasing the curing time, while the permanent deformation at the end of loading cycles and rutting potential increase by increasing the thermal equilibrium time. Additionally, the results of statistical analyses revealed that curing time and thermal equilibrium time change the rutting potential of asphalt mixtures.